Analysis between three gauging elements for irrigation systems in the province of Loja, Ecuador - Chamba Ontaneda, María (2018)
The objective of the study was to analyze the three typical elements of gauging in small channels and ditches for irrigation and to generate mathematical models that govern their hydrodynamic behavior. The devices analyzed were the Parshall gutter (CP), the neck gauge (AC) and the neckless gauge (AS). The research was developed in three phases. In the first stages, the discharges between 0 L/s and 10 L/s were determined, the number of measurements was nine for each element, with a total of 54 measurements, and finally the calibration equations, and the curves characterizing the flow meters were generated in the hydraulic bench of the laboratory. Results show a variation between 0.001 L/s and 0.002 L / s for discharges of less than 2 L/s; and from 0.008 L/s to 0.063 L/s for expenses between 2 L/s and 10 L/s. The equations and calibration curves were established to determine the flow rate in L/s as a function of the height of the tie rod in mm. The simulation of flow in the gauges was due to flow behavior under supercritical regime.